Metal material atmospheric corrosion humidity test method, galvanic sensor and preparation method
By using a galvanic sensor in the atmospheric corrosion test of metal materials, the metal material to be tested is used as the anode and the inert conductive material as the cathode, the current value is read to calculate the humidity, and the critical corrosion rate is used to define the effective wetting time, the existing test method is solved The problem of not being able to accurately obtain the wetting time of metal surfaces has achieved the accurate characterization of the wetting time of metal materials and the ability to apply to different atmospheric environments.
Patent Information
- Application Number
- CN202111071299.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-09-14
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2041-09-14
AI Technical Summary
Existing atmospheric corrosion testing methods for metal materials cannot accurately obtain the wetting time of metal surfaces and cannot adapt to the differences in different atmospheric environments.
The galvanic sensor is used, the metal material to be tested is used as the anode and the inert conductive material is used as the cathode. The humidity is calculated by reading the current value, and the effective wetting time is defined using the critical corrosion rate, which is suitable for environments in different regions.
It realizes accurate characterization of the wetting time of metal materials, improves the sensitivity and accuracy of testing, and is suitable for different atmospheric environments.
Smart Images

Figure CN113791031B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of atmospheric corrosion of metal materials, in particular to a method for testing atmospheric corrosion humidity of metal materials, a galvanic sensor, and a method for preparing the galvanic sensor. Background Art
[0002] More than 95% of the corrosion of metal materials in the atmosphere is electrochemical corrosion. The "thin liquid film corrosion theory" believes that electrochemical corrosion can only occur when a thin liquid film is formed on the metal surface in the atmosphere. Therefore, the wetting of the metal surface is the main controlling factor for corrosion. Domestic and foreign research has also shown that the relative humidity of the atmospheric environment will significantly affect the formation of thin liquid films, and thus affect the atmospheric corrosion of metal materials. Accurately grasping the wetting time of metal materials in the atmospheric environment is of great significance for studying the atmospheric corrosion process of metal materials and characterizing the dynamic laws.
[0003] The current national standards GB / T 19292 and ISO9223 for atmospheric corrosion of metal materials stipulate that the time to wetness (TOW) is the time when the metal surface is covered by adsorbents or (and) electrolyte films that can cause atmospheric corrosion. The time when the temperature is greater than 0°C and the relative humidity is greater than 80% (RH) is used to estimate the wetting time of the metal surface. This definition has been questioned by many scholars, who believe that it cannot accurately reflect the wetting time of the metal surface. In the actual corrosion process of metal materials, there are effective wetting times such as high temperature and low humidity and low temperature rain and fog that cannot be accurately characterized, and the above definition of wet time cannot adapt to the differences in atmospheric environment in various places.
[0004] How to accurately obtain the wetting time of the metal surface is a problem that needs to be solved urgently. Summary of the invention
[0005] The embodiments of the present invention provide a metal material atmospheric corrosion humidity testing method, a galvanic sensor and a preparation method thereof, so as to solve the problem that the existing testing methods and sensors cannot accurately obtain the wetting time of the metal surface.
[0006] According to a first aspect of an embodiment of the present invention, a galvanic sensor is provided.
[0007] In one embodiment, the galvanic sensor uses the metal material to be measured as the anode and the inert conductive material as the cathode;
[0008] The corrosion current density of the anode metal of the galvanic sensor is consistent with the corrosion current density of the metal material to be measured.
[0009] Optionally, the positive and negative electrodes of the galvanic sensor are insulated by insulating materials.
[0010] Optionally, the insulating material comprises epoxy resin.
[0011] Optionally, nano carbon powder is added to the insulating material.
[0012] Optionally, the positive and negative electrodes of the galvanic sensor adopt an upper and lower stacked structure, a comb structure, or a cross structure.
[0013] According to a second aspect of an embodiment of the present invention, a method for testing atmospheric corrosion humidity of a metal material is provided.
[0014] In one embodiment, the method for testing atmospheric corrosion humidity of metal materials comprises the following steps:
[0015] Place the galvanic sensor of any of the above embodiments at a detection site, read the current value of the galvanic sensor at fixed time intervals, and calculate the humidity of the metal material to be tested at the detection site. The humidity is equal to the proportion of the time when the read current value is greater than the corrosion current value corresponding to the critical corrosion rate in the whole year; the critical corrosion rate is the corrosion rate at the point where the corrosion rate changes fastest.
[0016] Optionally, the critical corrosion rate is obtained by the following steps:
[0017] In a laboratory environment, experiments were conducted under different relative humidity conditions to obtain the corrosion rates of the metal material samples to be tested under different relative humidity conditions;
[0018] Draw the corrosion rate and relative humidity curve, and the corrosion rate at the point where the corrosion rate changes fastest is the critical corrosion rate.
[0019] According to a third aspect of an embodiment of the present invention, a method for preparing a galvanic sensor is provided.
[0020] In one embodiment, the galvanic sensor preparation method is used to prepare a galvanic sensor according to any of the above embodiments, by adjusting the gap between the anode and cathode of the galvanic sensor and / or the insulation resistance of the insulating material, to prepare a galvanic sensor in which the corrosion current density of the anode metal of the galvanic sensor is consistent with the corrosion current density of the metal material to be measured.
[0021] Optionally, the gap between the positive and negative electrodes of the galvanic sensor is adjusted by adjusting the thickness of the insulating material.
[0022] Optionally, the insulation resistance of the insulating material is adjusted by adding nano carbon powder.
[0023] Optionally, the corrosion current density of the metal material to be tested is obtained by the following steps:
[0024] In a laboratory environment, an experiment is conducted under set relative humidity conditions to obtain the corrosion rate of the metal material sample to be tested under the set relative humidity conditions;
[0025] The corrosion rate of the metal material sample to be tested under the set relative humidity conditions is converted into the corrosion current density of the metal material to be tested under the set relative humidity conditions.
[0026] Optionally, the step of conducting an experiment under a set relative humidity condition to obtain a corrosion rate of the metal material sample to be tested under the set relative humidity condition specifically includes:
[0027] In a laboratory environment, an alternating humidity chamber is used to carry out corrosion tests on metal material samples to be tested. The relative humidity of the alternating humidity chamber is set to a fixed value. After the set corrosion time, the metal material samples to be tested are taken out, the corrosion products are removed, and the corrosion rate of the metal material samples to be tested under the humidity conditions is calculated based on the corrosion weight loss.
[0028] Optionally, the calculation formula for converting the corrosion rate of the metal material sample to be tested under the set relative humidity condition into the corrosion current density of the metal material to be tested under the set relative humidity condition is:
[0029] Where, M is the corrosion amount, unit is g;
[0030] I is the corrosion current density, unit is A / cm 2 ;
[0031] t is the detection time of the corrosion amount M, in seconds;
[0032] n is the molar mass of the metal material to be tested;
[0033] a is the common valence state of the anode metal;
[0034] S is the surface area of the metal sample to be tested, cm 2 .
[0035] Optionally, the corrosion current density of the anode metal of the galvanic sensor is obtained under the same corrosion test conditions as those for obtaining the corrosion current density of the metal material to be tested.
[0036] The technical solution provided by the embodiment of the present invention may have the following beneficial effects:
[0037] The galvanic sensor of the embodiment of the present invention uses the same metal as the metal material to be tested as the anode. The corrosion current density of the anode metal of the galvanic sensor is consistent with the corrosion current density of the metal material to be tested. When a thin liquid film exists between the cathode and the anode, that is, after the surface is wetted, the galvanic sensor can detect the current of the conductive loop between the cathode and the anode. Since the cathode is an inert conductive material and does not corrode, the detection current is the corrosion current generated by the corrosion of the anode metal, which is then converted into the corrosion current density of the anode metal, which can accurately characterize the wetting time of the metal and realize the sensitivity and accuracy of the galvanic sensor. Using an inert conductive material as the cathode avoids the influence of the corrosion of the cathode material on the detection result.
[0038] The metal material atmospheric corrosion humidity testing method of the embodiment of the present invention characterizes the corrosion caused by wetting during the corrosion process of the metal material through humidity. Compared with the single temperature and humidity defined by the wet time, it can more accurately reflect the actual corrosion process of the metal material and is applicable to different regions. The humidity is more strongly correlated with the atmospheric corrosion of the metal material.
[0039] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.
[0041] Figure 1 is a schematic structural diagram of a galvanic sensor according to an exemplary embodiment;
[0042] Figure 2 A flow chart of a method for testing atmospheric corrosion humidity of a metal material according to an exemplary embodiment;
[0043] Reference numerals:
[0044] 10. Anode metal; 20. Cathode metal; 30. Insulation layer; 40. Lead wire; 50. Epoxy resin layer. DETAILED DESCRIPTION
[0045] The following description and accompanying drawings fully illustrate the specific embodiments of this article so that those skilled in the art can practice them. Parts and features of some embodiments may be included in or replace parts and features of other embodiments. The scope of the embodiments of this article includes the entire scope of the claims, as well as all available equivalents of the claims. Herein, the terms "first", "second", etc. are only used to distinguish one element from another, without requiring or implying any actual relationship or order between these elements. In fact, the first element can also be called the second element, and vice versa. Moreover, the terms "include", "comprise" or any other variant thereof are intended to cover non-exclusive inclusion, so that the structure, device or equipment including a series of elements includes not only those elements, but also other elements that are not explicitly listed, or also include elements inherent to such structure, device or equipment. In the absence of more restrictions, the elements defined by the sentence "including one..." do not exclude the existence of other identical elements in the structure, device or equipment including the elements. Each embodiment is described in a progressive manner herein, and each embodiment focuses on the differences from other embodiments, and the same and similar parts between the embodiments can be referred to each other.
[0046] The terms "longitudinal", "lateral", "upper", "lower", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", etc. in this document indicate the orientation or position relationship based on the orientation or position relationship shown in the drawings, and are only for the convenience of describing this document and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operate in a specific orientation, and therefore cannot be understood as a limitation on the present invention. In the description of this document, unless otherwise specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a mechanical connection or an electrical connection, it can also be the internal communication of two elements, it can be a direct connection, or it can be an indirect connection through an intermediate medium. For ordinary technicians in this field, the specific meanings of the above terms can be understood according to specific circumstances.
[0047] As used herein, the term "plurality" means two or more than two, unless otherwise specified.
[0048] In this document, the character " / " indicates that the preceding and following objects are in an "or" relationship. For example, A / B means: A or B.
[0049] In this article, the term "and / or" is a description of the association relationship between objects, indicating that three relationships may exist. For example, A and / or B means: A or B, or, A and B.
[0050] Example 1
[0051] Figure 1 One embodiment of a galvanic sensor is shown.
[0052] In this embodiment, the galvanic sensor includes an anode 10 and a cathode 20. The galvanic sensor uses a metal material to be measured as an anode and an inert conductive material as a cathode, such as platinum, gold, graphite, etc. as the cathode. The corrosion current density of the anode metal of the galvanic sensor is consistent with the corrosion current density of the metal material to be measured. In this embodiment, the positive and negative electrodes use a mesh structure of upper and lower laminates, an insulating layer 30 is provided between the positive and negative electrodes, and a lead 40 connects the positive and negative electrodes to the two ends of an ammeter with zero internal resistance.
[0053] Optionally, an insulating material is used as an insulating layer 30 between the positive and negative electrodes of the galvanic sensor. By adjusting the gap between the positive and negative electrodes of the galvanic sensor, the corrosion current density of the anode metal of the galvanic sensor is made consistent with the corrosion current density of the metal material to be measured. Optionally, the gap between the positive and negative electrodes of the galvanic sensor is adjusted by adjusting the thickness of the insulating material. Optionally, an insulating material is coated between the positive and negative electrodes of the galvanic sensor, and the gap between the positive and negative electrodes is adjusted by adjusting the thickness of the coated insulating material. Optionally, the insulating material includes epoxy resin.
[0054] Optionally, nano-carbon powder is added to the insulating material, and the insulation resistance of the insulating material is adjusted by adding the nano-carbon powder to the insulating material. By adjusting the insulation resistance of the insulating material of the galvanic sensor, the corrosion current density of the anode metal of the galvanic sensor is consistent with the corrosion current density of the metal material to be measured.
[0055] Optionally, the positive and negative electrodes of the galvanic sensor may also adopt a comb-type structure or a cross-type structure.
[0056] Optionally, the anode metal, cathode metal, insulating layer, and lead wires of the thermocouple sensor are fixed by an epoxy resin layer 50 .
[0057] The galvanic sensor of the embodiment of the present invention uses the same metal as the metal material to be tested as the anode. The corrosion current density of the anode metal of the galvanic sensor is consistent with the corrosion current density of the metal material to be tested. When a thin liquid film exists between the cathode and the anode, that is, after the surface is wetted, the galvanic sensor can detect the current of the conductive loop between the cathode and the anode. Since the cathode is an inert conductive material and does not corrode, the detection current is the corrosion current generated by the corrosion of the anode metal, which is then converted into the corrosion current density of the anode metal, which can accurately characterize the wetting time of the metal and realize the sensitivity and accuracy of the galvanic sensor. Using an inert conductive material as the cathode avoids the influence of the corrosion of the cathode material on the detection result.
[0058] Example 2
[0059] Figure 2An embodiment of the metal material atmospheric corrosion humidity testing method of the present invention is shown.
[0060] In this embodiment, a method for testing the atmospheric corrosion humidity of metal materials includes the following steps: placing a galvanic sensor of any of the above embodiments at a detection site, reading the current value of the galvanic sensor at fixed time intervals, and calculating the humidity of the metal material to be tested at the detection site, wherein the humidity is equal to the proportion of the time when the read current value is greater than the corrosion current value corresponding to the critical corrosion rate to the time of the whole year; the critical corrosion rate is the corrosion rate at the point where the corrosion rate changes fastest.
[0061] The present invention proposes a new method for testing humidity of atmospheric corrosion of metal materials. Based on the atmospheric corrosion principle of metal materials, humidity is used to characterize the corrosion caused by wetting in the corrosion process of metal materials. Wetting will cause a surge in corrosion rate. The critical corrosion rate is used to define the time when metal materials produce effective wetting. Compared with the single temperature and humidity defined by the wet time, it can more accurately reflect the real corrosion process of metal materials and is applicable to different regions. The humidity is more strongly correlated with atmospheric corrosion of metal materials. The galvanic sensor uses the same metal as the metal material to be tested as the anode. The corrosion current density of the anode metal of the galvanic sensor is consistent with the corrosion current density of the metal material to be tested. When a thin liquid film exists between the anode and cathode, that is, after the surface is wetted, the galvanic sensor can detect the current of the conductive loop between the anode and cathode. Since the cathode is an inert conductive material and does not corrode, the detection current is the corrosion current generated by the corrosion of the anode metal, which is then converted into the corrosion current density of the anode metal, which can accurately characterize the wetting time of the metal.
[0062] Optionally, the above critical corrosion rate is obtained by the following steps:
[0063] In a laboratory environment, experiments were conducted under different relative humidity conditions to obtain the corrosion rates of the metal material samples to be tested under different relative humidity conditions;
[0064] Draw the corrosion rate and relative humidity curve, and the corrosion rate at the point where the corrosion rate changes fastest is the critical corrosion rate.
[0065] Optionally, in a laboratory environment, experiments are conducted under different relative humidity conditions to obtain the corrosion rate of the metal material sample to be tested under different relative humidity conditions, specifically including: using an alternating humidity chamber to conduct a corrosion test on the metal material sample to be tested, setting the relative humidity of the alternating humidity chamber to a fixed value, after a set corrosion time, removing the corrosion products according to GB / T 16545, and calculating the corrosion rate of the metal material sample to be tested under the set relative humidity conditions according to the corrosion weight loss. Optionally, the corrosion products are removed according to GB / T 16545.
[0066] Optionally, the step of converting the corrosion rate of the metal material sample to be tested under different relative humidity conditions into the corrosion current density of the metal material to be tested under different relative humidity conditions specifically includes: according to Faraday's law, converting the corrosion rate of the metal material sample to be tested into a corrosion molar amount, then converting it into the amount of electrons gained or lost, and finally converting it into the corrosion current density of the metal material to be tested. The corrosion current density calculation formula is:
[0067]
[0068] Where, M is the corrosion amount, unit is g;
[0069] I is the corrosion current density, unit is A / cm 2 ;
[0070] t is the detection time of the corrosion amount M, in seconds;
[0071] n is the molar mass of the metal material to be tested;
[0072] a is the common valence state of the anode metal, which is 2 for zinc, 3 for aluminum, 2 or 3 for steel, and 2 for copper;
[0073] S is the surface area of the metal sample to be tested, cm 2 .
[0074] Optionally, the calculation formula of the above embodiment is used to convert the critical corrosion rate of the metal material sample to be tested into a corrosion current, and obtain the corrosion current density corresponding to the critical corrosion rate of the metal material sample to be tested.
[0075] Connect the positive and negative electrodes of the galvanic sensor to the two ends of the zero-resistance ammeter through the lead wires. When there is a thin liquid film between the positive and negative electrodes, that is, when the surface is wetted, the galvanic sensor can detect the current of the conductive loop between the positive and negative electrodes. Since the cathode is an inert conductive material and does not corrode, the detection current is the corrosion current generated by the corrosion of the anode metal, which is then converted into the corrosion current density of the anode metal. The corrosion current density of the anode metal of the galvanic sensor is consistent with the corrosion current density of the metal material sample to be tested, which can accurately characterize the wetting time of the metal. Optionally, place the galvanic sensor in the test site, read the current value at a fixed time interval, and the time interval for reading the current value is less than or equal to 30 minutes. After at least one year of testing, calculate the time ratio of the time when the read current value is greater than the corrosion current value corresponding to the critical corrosion rate to the whole year, which is the humidity of the anode metal material used in the test site.
[0076] Before conducting a metal material atmospheric corrosion humidity test, it is necessary to prepare a galvanic sensor. A specific embodiment of the galvanic sensor preparation method and the metal material atmospheric corrosion humidity test method of the present invention is given below, wherein steps (1) to (3) are the galvanic sensor preparation method and the steps of solving the critical corrosion rate; step (4) is the metal material atmospheric corrosion humidity test method.
[0077] Step (1) uses an alternating humidity chamber to conduct corrosion tests on metal material zinc, with the zinc sample size being 100 mm×150 mm×3 mm. Under a constant temperature of 25° C., the relative humidity of the alternating humidity chamber is set to 50%, 60%, 70%, 80%, 90%, and 95% in sequence, and the corrosion tests are conducted for 1000 h, 800 h, 600 h, 400 h, 400 h, and 400 h, respectively. After removing the corrosion products according to GB / T16545, the corrosion rate under the humidity conditions was calculated according to the corrosion weight loss, and the corrosion rates of zinc under relative humidity of 50%, 60%, 70%, 80%, 90%, and 95% were: 0.00106μm / a, 0.00178μm / a, 0.02320μm / a, 0.1856μm / a, 1.4848μm / a, and 4.4543μm / a, respectively.
[0078] In the above steps, the relative humidity of the alternating heat and humidity box is set to increase successively, and the corrosion rate of the metal material sample to be tested under different relative humidity can be obtained. The corrosion rate of the metal material sample to be tested under different relative humidity can be used to draw a corrosion rate and relative humidity curve, and obtain the critical corrosion rate.
[0079] The above data were plotted into a curve, and after slope calculation, it was found that at 80% humidity, the corrosion rate changed fastest, and the corrosion rate of 0.1856 μm / a was the critical point.
[0080] Step (2), in step (1), at a relative humidity of 80%, the time is 400h, and the corrosion weight loss is 1.815mg, according to the above formula:
[0081] Where, M is the corrosion amount, unit is g;
[0082] I is the corrosion current density, unit is A / cm 2 ;
[0083] t is the detection time of the corrosion amount M, in seconds;
[0084] n is the molar mass of the metal material to be tested;
[0085] a is the common valence state of the anode metal, which is 2 for zinc;
[0086] S is the surface area of the zinc sample, cm 2 ;
[0087] After calculation, the corrosion current density I is 12.47nA / cm 2 .
[0088] Step (3), the galvanic sensor uses metal zinc as the anode and metal platinum as the cathode, using Figure 1 In the structure shown, the anode and cathode areas are both 10 cm 2 Epoxy resin glue is used as the insulating material. The gap between the anode and cathode is adjusted by the brushing process, and the insulation resistance is adjusted by adding nano-carbon powder. After the galvanic sensor is connected to a picoammeter, it is tested in an alternating heat and humidity chamber so that the current value detected by the galvanic sensor meets the current value in the above-mentioned metal zinc sample test process. After adjustment, when the gap of the galvanic sensor is controlled at 10-30μm and the insulation resistance is controlled at 1-3KΩ, the corrosion current density of the anode metal of the galvanic sensor is consistent with the corrosion current density of the actual sample. At 80% humidity, the current obtained by the galvanic sensor is 12nA.
[0089] Step (4), connect the above galvanic sensor to the tester and storage device, place it in Jinan, and set the test interval to 10 minutes. After 1 year of testing, the percentage of corrosion current values greater than 12nA in the whole year was statistically calculated, and the result was 0.2352, that is, the humidity of atmospheric corrosion of metal zinc in Jinan area was 0.2352.
[0090] Example 3
[0091] In another embodiment, the present invention further proposes a method for preparing a galvanic sensor, which is used to prepare a galvanic sensor for any of the above embodiments, including: preparing a galvanic sensor in which the corrosion current density of the anode metal of the galvanic sensor is consistent with the corrosion current density of the metal material to be measured by adjusting the gap between the anode and cathode of the galvanic sensor and / or the insulation resistance of the insulating material.
[0092] By adjusting the gap between the anode and cathode of the galvanic sensor and / or the insulation resistance of the insulating material, the corrosion current density of the anode metal of the galvanic sensor is made consistent with the corrosion current density of the metal material to be measured. The anode and cathode of the galvanic sensor are respectively connected to the two ends of an ammeter with zero internal resistance through leads. When a thin liquid film exists between the anode and cathode, that is, the surface is wetted, the galvanic sensor can detect the current of the conduction loop between the anode and cathode. Since the cathode is an inert conductive material and does not corrode, the detected current is the corrosion current generated by the corrosion of the anode metal, which is then converted into the corrosion current density of the anode metal, which can accurately characterize the wetting time of the metal and realize the sensitivity and accuracy of the galvanic sensor.
[0093] Optionally, the gap between the positive and negative electrodes of the galvanic sensor is adjusted by adjusting the thickness of the insulating material. Optionally, an insulating material is applied between the positive and negative electrodes of the galvanic sensor, and the gap between the positive and negative electrodes is adjusted by adjusting the thickness of the applied insulating material. Optionally, the insulating material includes epoxy resin.
[0094] Optionally, the insulation resistance of the insulating material is adjusted by adding nano carbon powder.
[0095] Optionally, the corrosion current density of the metal material to be tested is obtained by the following steps:
[0096] In a laboratory environment, the experiment is carried out under set relative humidity conditions to obtain the corrosion rate of the metal material sample to be tested under the set relative humidity;
[0097] The corrosion rate of the metal material sample to be tested under the set relative humidity conditions is converted into the corrosion current density of the metal material to be tested under the set relative humidity conditions.
[0098] The relative humidity condition can be set to any humidity condition, such as setting the relative humidity of the alternating heat and humidity chamber to 50%, 60%, 70%, 80%, 90% or 95%, and subjecting the corrosion test to 1000h, 800h, 600h, 400h, 400h or 400h. More specifically, the relative humidity can be set to 60% and subjecting the corrosion test to 800h, or the relative humidity can be set to 70% and subjecting the corrosion test to 600h, or the relative humidity can be set to 80% and subjecting the corrosion test to 400h, etc.
[0099] Optionally, the step of conducting an experiment under a set relative humidity condition in a laboratory environment to obtain the corrosion rate of the metal material sample to be tested under the set relative humidity specifically includes: in a laboratory environment, using an alternating humidity chamber to conduct a corrosion test on the metal material sample to be tested, setting the relative humidity of the alternating humidity chamber to a fixed value, after a set corrosion time, removing the corrosion products according to GB / T 16545, and calculating the corrosion rate of the metal material sample to be tested under the humidity condition according to the corrosion weight loss. Optionally, the corrosion products are removed according to GB / T16545.
[0100] Optionally, the calculation formula for converting the corrosion rate of the metal material sample to be tested under the set relative humidity condition into the corrosion current density of the metal material to be tested under the set relative humidity condition is:
[0101] Where, M is the corrosion amount, unit is g;
[0102] I is the corrosion current density, unit is A / cm 2 ;
[0103] t is the detection time of the corrosion amount M, in seconds;
[0104] n is the molar mass of the metal material;
[0105] a is the common valence state of the anode metal;
[0106] S is the surface area of the metal sample to be tested, cm 2 .
[0107] Optionally, the process of obtaining the corrosion current density of the anode metal of the galvanic sensor is completed under the same corrosion test conditions as those for obtaining the corrosion current density of the metal material to be tested, for example, in a laboratory environment, an alternating heat and humidity chamber is used to perform the same corrosion test on the galvanic sensor as the test sample.
[0108] The present invention is not limited to the structures which have been described above and shown in the drawings, and various modifications and changes may be made without departing from the scope thereof. The scope of the present invention is limited only by the appended claims.
Claims
1. A method for testing atmospheric corrosion humidity of metal materials, characterized in that: The following steps are involved: A galvanic sensor is placed at a testing site, and the current value of the galvanic sensor is read at regular time intervals to calculate the humidity of the metal material to be tested at the testing site. The humidity is equal to the proportion of time in a year when the read current value is greater than the corrosion current value corresponding to the critical corrosion rate; the critical corrosion rate is the corrosion rate at the point where the corrosion rate changes fastest; The galvanic sensor uses the metal material to be measured as the anode and an inert conductive material as the cathode; the corrosion current density of the anode metal of the galvanic sensor is consistent with the corrosion current density of the metal material to be measured.
2. A method for testing atmospheric corrosion humidity of metal materials according to claim 1, characterized in that: The positive and negative electrodes of the galvanic sensor are insulated by insulating materials.
3. A method for testing atmospheric corrosion humidity of metal materials according to claim 2, characterized in that: The insulating material includes epoxy resin.
4. A method for testing atmospheric corrosion humidity of metal materials according to claim 2, characterized in that: Nano carbon powder is added into the insulating material.
5. A method for testing atmospheric corrosion humidity of metal materials according to claim 1, characterized in that: The anode and cathode of the galvanic sensor adopt an upper and lower laminated structure, a comb structure, or a cross structure.
6. A method for testing atmospheric corrosion humidity of metal materials according to claim 1, characterized in that: The critical corrosion rate is obtained by the following steps: conducting experiments under different relative humidity conditions in a laboratory environment to obtain the corrosion rates of the metal material samples to be tested under different relative humidity conditions; Draw the corrosion rate and relative humidity curve. The corrosion rate at the point where the corrosion rate changes fastest is the critical corrosion rate.
7. A method for testing atmospheric corrosion humidity of metal materials according to claim 1, characterized in that: The galvanic sensor uses a metal material to be measured as an anode and an inert conductive material as a cathode; the corrosion current density of the anode metal of the galvanic sensor is consistent with the corrosion current density of the metal material to be measured; the anode and cathode of the galvanic sensor are insulated by an insulating material; the insulating material includes epoxy resin; nano-carbon powder is added to the insulating material; the anode and cathode of the galvanic sensor adopt an upper and lower laminated structure, a comb structure, or a cross structure; The preparation method of the galvanic sensor comprises: preparing a galvanic sensor in which the corrosion current density of the anode metal of the galvanic sensor is consistent with the corrosion current density of the metal material to be measured by adjusting the gap between the anode and the cathode of the galvanic sensor and / or the insulation resistance of the insulating material; The corrosion current density of the metal material to be tested is obtained by the following steps: conducting an experiment under a set relative humidity condition in a laboratory environment to obtain the corrosion rate of the metal material sample to be tested under the set relative humidity condition; Converting the corrosion rate of the metal material sample to be tested under the set relative humidity condition into the corrosion current density of the metal material to be tested under the set relative humidity condition; The step of conducting an experiment under set relative humidity conditions to obtain the corrosion rate of the metal material sample to be tested under the set relative humidity conditions specifically includes: in a laboratory environment, using an alternating humidity chamber to perform a corrosion test on the metal material sample to be tested, setting the relative humidity of the alternating humidity chamber to a fixed value, taking out the metal material sample to be tested after a set corrosion time, removing corrosion products, and calculating the corrosion rate of the metal material sample to be tested under the humidity conditions based on the corrosion weight loss.
8. A method for testing atmospheric corrosion humidity of metal materials according to claim 7, characterized in that: The gap between the anode and cathode of the galvanic sensor is adjusted by adjusting the thickness of the insulating material.
9. A method for testing atmospheric corrosion humidity of metal materials according to claim 7, characterized in that: The insulation resistance of the insulating material is adjusted by adding nano-carbon powder.
10. A method for testing atmospheric corrosion humidity of metal materials according to claim 7, characterized in that: The calculation formula for converting the corrosion rate of the metal material sample to be tested under the set relative humidity condition into the corrosion current density of the metal material to be tested under the set relative humidity condition is: Where M is the corrosion amount, unit is g; I is the corrosion current density, unit is A / cm 2 ; t is the detection time of the corrosion amount M, in seconds; n is the molar mass of the metal material to be measured; a is the common valence state of the anode metal; S is the surface area of the metal material sample to be tested, unit is cm 2 .
11. A method for testing atmospheric corrosion humidity of metal materials according to claim 7, characterized in that: The corrosion current density of the anode metal of the galvanic sensor is obtained under the same corrosion test conditions as those for obtaining the corrosion current density of the metal material to be tested.
Citation Information
Patent Citations
Couple corrosion sensor
CN103018299A
